Preoptic Area Activation and Vasotocin Involvement in the Reproductive Behavior of a Weakly Pulse-Type Electric Fish, Brachyhypopomus gauderio - Pouso, Paula; Cabana, Álvaro; Goodson, James L.; Silva, Ana (Frontiers in Integrative Neuroscience, 2019)
Social behavior exhibits a wide diversity among vertebrates though it is controlled by a conserved neural network, the social behavior network (SBN). The activity of the SBN is shaped by hypothalamic nonapeptides of the vasopressin-oxytocin family. The weakly electric fish Brachyhypopomus gauderio emits social electrical signals during courtship. Three types of vasotocin (AVT) cells occur in the preoptic area (POA), one of the SBN nodes. In this study, we aimed to test if POA neurons of the nucleus preopticus ventricularis anterior (PPa) and posterior (PPp), and in particular AVT+ cells, were activated by social stimuli using a 2-day behavioral protocol. During the first night, male-female dyads were recorded to identify courting males. During the second night, these males were divided in two experimental conditions: isolated and social (male with a female). Both AVT cells and the cellular activation of the POA neurons (measured by FOS) were identified. We found that the PPa of social males showed more FOS+ cells than the PPa of isolated males, and that the PPa had more AVT+ cells in social males than in isolated males. The double-immunolabeling for AVT and FOS indicated the activation of AVT+ neurons. No significant differences in the activation of AVT+ cells were found between conditions, but a clear association was observed between the number of AVT+ cells and certain behavioral traits. In addition, a different activation of AVT+ cell-types was observed for social versus isolated males. We conclude that the POA of B. gauderio exhibits changes induced by social stimuli in reproductive context, involving an increase in AVT production and a different profile activation among AVT+ cell populations.